2018
DOI: 10.1186/s12870-018-1518-8
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in a CENTRORADIALIS homolog contributed to cluster fruiting and early maturity in cotton

Abstract: BackgroundPlant architecture and the vegetative-reproductive transition have major impacts on the agronomic success of crop plants, but genetic mechanisms underlying these traits in cotton (Gossypium spp.) have not been identified.ResultsWe identify four natural mutations in GoCEN-Dt associated with cluster fruiting (cl) and early maturity. The situ hybridization shows that GhCEN is preferentially expressed in cotton shoot apical meristems (SAM) of the main stem and axillary buds. Constitutive GhCEN-Dt overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…This concept follows the successful introduction of sp into Chinese cotton lines (Fig. 2), which are high performing and grown farther north than any functional SP cultivars (84). Another benefit of earlier flowering is evasion of early freezing temperatures at the end of short growing seasons or late-season drought, as has already been proposed for wheat (85).…”
Section: Expanding Agricultural Horizons: Feeding Humans Not Their Livestockmentioning
confidence: 98%
“…This concept follows the successful introduction of sp into Chinese cotton lines (Fig. 2), which are high performing and grown farther north than any functional SP cultivars (84). Another benefit of earlier flowering is evasion of early freezing temperatures at the end of short growing seasons or late-season drought, as has already been proposed for wheat (85).…”
Section: Expanding Agricultural Horizons: Feeding Humans Not Their Livestockmentioning
confidence: 98%
“…This phenotype was found simultaneously by us and two other independent research groups to be due to mutations in a cotton ortholog of TFL1/SP/CEN . Although all three research groups identified the same gene, it was given different names by each ( Liu et al, 2018 ; Si et al, 2018 ; Chen et al, 2019 ). Because the amino acid sequence deduced from this gene has the highest similarity with the tomato SP protein, this paper describes it as the cotton SP gene ( McGarry et al, 2016 ; Si et al, 2018 ).…”
Section: Cotton Terminal Flower1/self-pruning/centroradialis Genes Re...mentioning
confidence: 99%
“…Overexpression of the GhSP gene in cotton inhibited flower bud growth, indicating that GhSP plays a key role in regulating flower bud differentiation and determinate growth ( Chen et al, 2019 ). In situ hybridization revealed that GhSP was preferentially expressed in the meristems of cotton main stems and axillary buds ( Liu et al, 2018 ). Overexpression of GhSP inhibited the transition from vegetative to reproductive branch formation ( Liu et al, 2018 ; Si et al, 2018 ).…”
Section: Cotton Terminal Flower1/self-pruning/centroradialis Genes Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this complexity, no flowering‐related genes were isolated from cotton by map‐based cloning. So far, only a small number of genes have been cloned by reverse genetics and preliminarily verified that they may control flowering in cotton such as GhFPF1 (Wang et al ., 2014), GhSOC1 (Zhang et al ., 2016), GhCEN‐DT (Liu et al ., 2018) and GhAAI66 (Qanmber et al ., 2019). Flower bud differentiation is an important character influencing the early maturity of cotton varieties.…”
Section: Introductionmentioning
confidence: 99%